f ( x ) = 1 + x + x 2 1
For the function f ( x ) as described above, then d x 6 d 6 f ( x ) can be represented as
b a sin c ( arctan ( e x + f d ) ) sin ( g ⋅ arctan ( e x + f d ) )
where a , b , c , d , e , f , g are integers independent of x . for g cd ( a , b ) = 1 and d square free.
Evaluate a + b + c + d + e + f + g .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Use partial fraction decomposition (PFD) via "Covering Method" on f ( x ) . We notice it has a complex pole-pair: f ( x ) = ( x + 2 1 ) 2 + 4 3 1 = ( x − x 0 ) ( x − x 0 ∗ ) 1 PFD = x − x 0 A + x − x 0 ∗ A ∗ ∣ ∣ ∣ ∣ ∣ x 0 = − 2 1 + i 2 3 , A = − 3 i To simplify the 6'th derivative into sines and arctangents, we write x − x 0 = ∣ x − x 0 ∣ e i φ in polar coordinates: f ( 6 ) ( x ) φ = 6 ! ( − 1 ) 6 [ ( x − x 0 ) 7 A + ( x − x 0 ∗ ) 7 A ∗ ] = 6 ! ⋅ 2 ℜ { ( x − x 0 ) / A } = 3 ∣ x − x 0 ∣ 7 − 6 ! ⋅ 2 ℜ { i e − i 7 φ } : = arct g 2 ( − 2 3 , x + 2 1 ) = − arct g 2 ( 3 , 2 x + 1 ) ⇒ sin ( φ ) = ∣ x − x 0 ∣ − 2 3 With sin ( φ ) we can eliminate ∣ x − x 0 ∣ from the derivative. Collecting coefficients from φ , we get d = 3 , e = 2 , f = 1 and finally f ( 6 ) ( x ) = 3 8 6 ! ⋅ ( − 2 ) 8 sin 7 ( φ ) sin ( 7 φ ) = 9 2 0 4 8 0 sin 7 ( φ ) sin ( 7 φ ) ⇒ a + … + g = 2 0 5 0 9
Problem Loading...
Note Loading...
Set Loading...
Here is a generalised solution
Consider the function f ( x ) = x 2 + a 2 1
Noting that the n th derivative of f ( x + c ) ∀ c ∈ R is essentially identical to the n th derivative of f ( x ) , we proceed without loss of generality.
Let x = a cot θ ⇔ θ = tan − 1 x a and differentiate both sides implicitly to obtain d x d θ = − a sin 2 θ
Rewrite f ( x ) in terms of θ to obtain f ( x ) = a 2 sin 2 θ and differentiate using the chain rule to obtain
d x d ( f ( x ) ) = − a 3 2 sin θ cos θ × sin 2 θ = ( − a ) 3 1 × sin 2 θ × sin 2 θ
The pattern is apparent at this stage, if you do not yet see it, differentiate once more and simplify.
Out of brevity, I will jump straight to the propositional statement for the n th derivative of f ( x ) .
P ( n ) : ( d x ) n d n ( f ( x ) ) = ( − a ) n + 2 n ! × sin ( n + 1 ) θ × sin n + 1 θ ∀ n ∈ N
The case n = 0 is a trivial case, and we have obtained n = 1 , so we may take the inductive step.
Assume the statement holds true for some n ∈ N .
P ( n ) : ( d x ) n d n ( f ( x ) ) = ( − a ) n + 2 n ! × sin ( n + 1 ) θ × sin n + 1 θ
Then we differentiate both sides w.r.t. x using the product and chain rules to obtain the next derivative.
( d x ) n d n ( f ( x ) ) = ( − a ) n + 2 n ! × [ ( n + 1 ) cos ( n + 1 ) θ × sin n + 1 θ + ( n + 1 ) sin ( n + 1 ) θ × sin n θ cos θ ] × − a sin 2 θ
Factor out n + 1 and merge it with the already existing n ! , and likewise for sin n θ with sin 2 θ and ( − a ) n + 2 with − a
( d x ) n d n ( f ( x ) ) = ( − a ) n + 3 ( n + 1 ) ! × [ cos ( n + 1 ) θ × sin θ + sin ( n + 1 ) θ × cos θ ] × sin n + 2 θ
Use the reverse angle sum expansion identity sin a cos b + sin b cos a ≡ sin ( a + b )
( d x ) n d n ( f ( x ) ) = ( − a ) n + 3 ( n + 1 ) ! × sin ( n + 2 ) θ × sin n + 2 θ ⇒ P ( n + 1 )
This proves the propositional statement for n + 1 , provided it is true for n .
As the proposition is true for n = 0 and n = 1 , by the Axiom of Induction, the proposition is true ∀ n ∈ N
Setting c = 2 1 , a = 2 3 , n = 6 , and noting θ = tan − 1 2 x + 1 3 we obtain:
( d x ) 6 d ( f ( x + 2 1 ) ) = 3 4 6 ! × 2 8 × sin 7 ( tan − 1 2 x + 1 3 ) × sin 7 ( tan − 1 2 x + 1 3 ) = 9 2 0 4 8 0 × sin 7 ( tan − 1 2 x + 1 3 ) × sin 7 ( tan − 1 2 x + 1 3 )
So we have a + b + c + d + e + f + g = 2 0 4 8 0 + 9 + 7 + 2 + 3 + 1 + 7 = 2 0 5 0 9